Quality assessment of health care services in patients’ and medical staff’s opinion - Rybarczyk, Anna; Marczak, Michał (Polish Journal of Public Health, 2011)
Introduction. The determination of standards and assuring high quality services constitute main requirements for the units functioning in the health care services market. These entities comprise health care units which prioritize the delivery of high quality services. Such services mean health, reliance, safety as well as patient’s life. Aim. The aim of this work is a partial assessment of the quality of medical services which was effectuated in three wards of the two clinical hospitals of Medical University of Lodz. Material and methods. The research was directed towards medical staff and patients who were surveyed. The research included 101 respondents. Results. The results regarding the patient’s first contact with the personnel in the health care unit show a high level of satisfaction from the services. The patients are satisfied with the kindness, empathy and the ability to understand the needs and expectations of the patients. The aspects of quality: providing the comprehensible and complete information about patient’s health, the information regarding the risk connected with the undertaken treatment, the possibility to choose the form of treatment, were assessed much less favorably. Half of the medical staff is convinced that patients receive comprehensible and complete information about their health, the majority of them is assured that a patient does not decide which diagnostic and therapeutic unit to choose. The results show that the personnel do not violate patient’s rights to receive good care and to be treated with respect and dignity. More than half of the interrogated patients were not informed about their rights. Conclusions. The lowest assessed aspects of quality such as the possibility to receive complete information regarding patient’s health, risk connected with undertaken treatment and the possibility to choose the diagnostic and therapeutic unit, have a great impact on the level of risk acceptance in the health care area, which is much too high in the Polish health care system.